Extraction of secondary metabolites responsible for biological activities from the leaf callus of Tetracera rosiflora - Seudi, Ariane K.; Muanyishay, Christophe L.; Muabu, Arsène K.; Bulubulu, Freddy O.; Kazadi, Théodore K.; Amogu, Jean-Jacques D.; Tshiongo, Christian M.; Taba, Nicolas K.; Ntumba, Josephine K. (Orapuh Journal, 2025)
Introduction Tetracera rosiflora Gilg is a plant used in traditional Congolese medicine for its multiple virtues, including antidiabetic effects. However, this species is threatened with extinction due to habitat destruction and overexploitation of its natural resources. Purpose To address this issue, it is essential to explore alternative methods for producing its bioactive secondary metabolites, such as through in vitro culture. Methods This study aimed to extract the secondary metabolites responsible for biological activities (antidiabetic and anti-amylase) and compare their concentrations in both the wild plant and in vitro-derived callus. A phytochemical screening was conducted on the leaves and various extracts of T. rosiflora. Results In vitro culture of T. rosiflora yielded higher callogenesis rates for stem explants on MS + 2,4-D medium (48%) and for leaf explants on MS + AIB + BAP medium (50%). Quantification of polyphenols revealed that the wild plant contained significantly higher levels (28.13 ± 1.18 mg gallic acid equivalent/g dry mass) compared to the callus, which showed a maximum of 1.41 ± 0.0045 mg gallic acid equivalent/g dry mass. Conclusion This study contributes to the potential amplification of valuable secondary metabolites from endangered wild species through callogenesis techniques.